Juridical analysis in the application of the principle of paying polluters in the case of screen printing waste pollution in Denpasar - Mahadewi, Kadek Julia (Institute Of computer Science (IOCS), 2024)
The basic foundation of environmental management in the 1945 Constitution article 28 H which is the right of the community to get a healthy environment is emphasized by the existence of the UUPPLH which makes rules on environmental management which of course can harm the surrounding environment. The use of the principle of polluters who pay in the pollution of screen printing waste in Tukad Badung by Mila Boutique refers to article 2 of the UUPPLH, this is the need to handle in answering the problems that occur this violation is evidenced by illegality, environmental pollution and the responsibility of the perpetrator. This research method uses normative methods, legal and case approaches, and primary and secondary legal sources. The technique of collecting legal materials for literature studies and the analysis technique is qualitative description. Pollution of screen printing waste occurs with a change in color throughout the body, this results in environmental pollution that endangers human health and the environmental order. The need to enforce environmental pollution issues for the sake of a sustainable future.